Resilient Residential Developments: Design Strategies for High-Density Cities - Thilakaratne, Ruffina; Liang, Calvin Zhiyong (MAJ - Malaysia Architectural Journal, 2025)
Mega cities face the next ‘global emergency’ when the global population is projected to reach 9.7 billion by the mid-century, leading to interconnected web of concerns and challenges such as escalating built density, greenhouse gas emissions and climate change impacts, epidemic threats, liveability of cities, and the decline of natural habitats and biodiversity. Hong Kong population is projected to increase up to 8.96 million by 2050. Due to challenging topography, currently 7.49 million population occupies around 275sqm developed land area with densities in some areas exceeding 57,000 per sqkm. Due to high-rise high- densities, lack of urban open spaces, Urban Heat Island (UHI) effect, poor air quality and low wind velocity have become serios public health concerns effecting Hong Kong’s liveability. This scenario certainly warrants revolutionary approaches. This paper focused on the aspects directly related to high-density cities and associated impacts such as limited land area for future developments, urban greenery, urban porosity, poor urban ventilation and daylight penetration to street levels to facilitate user comfort. This study compared existing residential typology with three proposed variations using simulation platforms for urban ventilation, shadow analysis and daylight performance analysis. Results were validated with district level microclimatic data, and literature reviews. Findings indicate the prospects for much higher vertical developments with no adverse impacts on daylight penetration, shading and wind flow. Wind flow and shading effect were improved with taller towers with wider spacing, improving microclimate around open podiums making them desirable for use during hot summer months.